Pengaruh Abusive Customer Behaviour terhadap Turnover Intention Karyawan Retail di Jabodetabek - Karisma Amirahfatin; Tantri Yanuar Rahmat Syah (JUDICIOUS, 2023)
This study aims to investigate the relationship between abusive customer behavior, job satisfaction, psychological well-being, and turnover intention among retail employees in several malls in the Greater Jakarta area, Indonesia. Data collection was carried out online using a Likert scale. The population in this study were frontline employees (Sales/SPG, Cashier, and Customer Service) who worked at retail stores in the Greater Jakarta area, with a total of 126 respondents. The research method used is quantitative research with Lisrel SEM analysis. The results of the study show that abusive customer behavior has a negative effect on employee job satisfaction. Furthermore, job satisfaction has a negative effect on turnover intention. However, abusive customer behavior does not have a positive effect on turnover intention. In addition, it was found that job satisfaction has a positive effect on psychological well-being. However, psychological wellbeing does not have a negative effect on turnover intention. In the context of the retail industry, this study emphasizes the importance of increasing employee job satisfaction to reduce turnover intention. This research contributes to the understanding of abusive customer behavior, job satisfaction, psychological well-being, and turnover intention in the context of the retail industry in Indonesia. The practical implication of this research is the importance of retail companies to pay attention to the protection and support of employees in dealing with bad customer behavior. Future research can broaden the scope of variables and a wider sample to deepen understanding of the factors that influence turnover intention in the retail sector in Indonesia.